REVIEW OF SCHEFFLER REFLECTOR - Mr. Aniket M. Akhade,; Dr. Rupesh J. Patil, (International Journal of Innovations in Engineering Research and Technology, 2021)
Scheffler reflector is one of thevarious methods of harvesting the solar energy. Scheffler fixed focusconcentrators are successfully used for medium temperature applications in different parts of the world. Theseconcentrators are taken as lateral sections of paraboloids and provide fixed focus away from the path of incidentbeam radiationsthroughout the year.Parabolic Scheffler Reflectors can provide us high temperature heat for alltypes of cooking, steam generation and many other applications.In this paper differentSchefflersystems arereviewed.